The impact of health care: on character formation, ethical education, and the communication of values in late modern pluralistic societies - Welker, Michael; Winkler, Eva C.; Witte, John; Pickard, Stephen K. (Evangelische Verlagsanstalt, 2023)
Pluralism has become the defining characteristic of many modern societies. Not only a plurality of individual and social claims and activities gain impacts on societal life. A creative pluralism of institutions and their norms profoundly shape our moral commitments and character – notably the family, the market, the media, and systems of law, religion, politics, research, education, health care, and defense. In the theoretical, empirical, and historical contributions to this volume, specialists on medicine, medical ethics, psychology, theology and health care discuss the many challenges that major transformations in their areas of expertise pose to the communication and orientation in late modern pluralistic societies. Contributors come from Germany, the USA and Australia.
Keywords: Aufsatzsammlung; Christliche Erziehung; Werterziehung; Sittliche Erziehung; Charakterbildung; Medizinische Ethik; Pluralistische Gesellschaft